Investigation of Layer Thickness Effects on Mechanical Properties of PLA Using FDM Additive Manufacturing - Abdullah F. Alhuzaim (Yanbu Journal of Engineering and Science)
This study explores the influence of layer thickness on the mechanical properties of Polylactic Acid (PLA) fab- ricated using Fused Deposition Modeling (FDM) additive manufacturing. By systematically varying the layer thickness, the aim to understand how these changes affect tensile strength, elasticity, and overall structural integrity of the printed components. The research employs a series of controlled experiments, utilizing standardized testing procedures to mea- sure and analyze the mechanical performance of PLA specimens. Results indicate significant variations in mechanical properties correlating with different layer thicknesses, providing valuable insights for optimizing print parameters in FDM processes. These findings contribute to the broader knowledge base, guiding the design and manufacturing of more robust and reliable 3D-printed objects.